Teacher Leading Program in Improving Learning Transformation in South Sorong District - Toar, Rendy C.; Rawis, Joulanda A. M.; Usoh, Elni J. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to describe the effectiveness of the role of the Leading Teacher in improving learning transformation and identifying supporting and inhibiting factors in the implementation of the Leading Teacher Program in South Sorong Regency. This study uses a qualitative approach with data collection techniques through interviews, observations, and documentation in several schools implementing the program. The results of the study indicate that Leading Teachers have a strategic role in transforming learning through role models, increasing student motivation and competence, and strengthening learning communities in schools. Supporting factors for program implementation include transformative principal leadership and internal teacher motivation. Meanwhile, inhibiting factors include limited facilities and infrastructure, difficult-to-access geographical conditions, and lack of support from several principals and fellow teachers. This study recommends strengthening local policies, improving educational facilities, and developing the capacity of principals as learning leaders in order to optimize the role of Leading Teachers in remote areas.